Personal growth experiences of countertransference among Malaysian counsellors: a phenomenological study - Lee, Wei Lu; Lau, Poh Li; Chan, Siaw Leng (Univ. of Malaya, 2023)
Countertransference has become a multifaceted, multidimensional, all-encompassing clinical phenomenon. The current study aimed to understand the positive growth experiences of countertransference in six Malaysian counsellors by utilising a transcendental phenomenological design. Moustakas's eight data analysis steps were applied in the data analysis. The themes that emerged from in-depth interviews included (1) improved self-confidence, (2) skill enhancement, (3) acceptance, (4) openness, (5) self-kindness, (6) a deeper understanding of self, and (7) redefining the meaning. The findings demonstrated that the insights gained through the countertransference experiences added positive values to their professional and personal lives. This study also revealed in-depth descriptions of the positive transformations from countertransference among Malaysian counsellors. This study has significant implications for counselling practices holistically.